Anti-fascism in a Global Perspective Transnational Networks, Exile Communities, and Radical Internationalism - Braskén, Kasper; Copsey, Nigel; Featherstone, David (Taylor & Francis, 2021)
Democracy; Extreme; Parties; Portugal; Portuguese; Right